2019
DOI: 10.35180/gse-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Properties of Fly Ash Based Microfiltration Membrane Support

Abstract: The main aim of this work was to prepare a ceramic membrane support applied directly to microfiltration of industrial wastewater using a simple and cheap method. Microfiltration (MF) supports were prepared using fly ash as a dominant material and by addition of natural inorganic materials kaolin and claystone. These powders were mixed with alkali solution in order to prepare paste suitable for extrusion. The extruded tubes dried at room temperature and sintered at 1000°C showed great chemical resistance. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The main steps of the processing route for support preparation, used in this work, is described in Figure 1. Chemical analysis of the materials is given in our previous article [8].…”
Section: Support Preparation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The main steps of the processing route for support preparation, used in this work, is described in Figure 1. Chemical analysis of the materials is given in our previous article [8].…”
Section: Support Preparation Processmentioning
confidence: 99%
“…The alkaline activation of aluminosilicates can be defined as a chemical process that leads to a rapid change in the specific structurepartially or totally amorphous which is very similar to the chemistry involved in the synthesis of large group of zeolites [4,5]. It was found that fly ash based geopolymer matrix after heat treatment to 1000 °C creates a large number of small highly-dispersed pores and shows excellent results with high compressive strength, high temperature, and resistance to harsh environments [6][7][8]. Such characteristics are very useful for ceramic membranes supports.…”
Section: Introductionmentioning
confidence: 99%